Paleoecology and paleoenvironments of Permian bivalves of the Serra Alta Formation, Brazil: Ordinary suspension feeders or Late Paleozoic Gondwana seep organisms? - Matos, Suzana Aparecida [UNESP]; Warren, Lucas Verissimo [UNESP]; Fuersich, Franz Theodor; Alessandretti, Luciano; Assine, Mario Luis [UNESP]; Riccomini, Claudio; Simões, Marcello Guimarães [UNESP] (Elsevier B.V., 2017)
This is the first record of a Permian seep deposit and an associated, morphologically bizarre, bivalve-dominated fauna from the Passa Dois Group, Parana Basin, Brazil. Shales of the outer-shelf facies of the Serra Alta Formation preserve a low-diversity but high-abundant, large-sized bivalve fauna with unusual morphologies inside discoidal carbonate concretions. The bivalves are about ten times larger than tiny bivalves found scattered in laterally equivalent mudstones of the same unit. Intercalated between two concretion-bearing horizons, a cm-thick, sheet-like, disrupted, brecciated, partially silicified carbonate layer with microbially-induced lamination is recorded. In some areas, the carbonate layer shows vertical structures formed by injections of mud mixed with white limestone clasts and microbial linings. Immediately above this, silicified mudstones preserve small domal structures (= mounds) with a slightly depressed center. Monospecific concentrations of closed articulated shells of Tambaquyra camargoi occur at the base of these domes. Carbon-isotope (delta C-13) values from the shells, brecciated carbonates, and fossil-rich concretions are all depleted (negative values similar to -6.1 to -7.6 parts per thousand). Combined taphonomic, sedimentological, petrographic, geochemical and paleontological data suggest that the disrupted, brecciated carbonate and associated fauna and domes may have formed by an exudation system. Indeed, this interval of the Serra Alta Formation is similar to 8.7 m above the contact with the underlying, oil-rich Irati Formation. This unit has very high total organic carbon (up to 23%) values and high sulphur contents, supporting the interpretation of the lithological and paleontological features as result of seepage of organic compounds at the seafloor. Where the gases and hydrocarbons escaped, the seabed was colonized by, at least facultatively, chemosymbiotic bivalves. The species above belong to a highly endemic group of pachydomids that were shallow infaunal bivalves (SIB). Hence, they are not related to classical bivalves with extant representatives, which are chemosymbionts. This may reflect an extreme adaptive radiation and repopulation of anoxic-dysoxic bottoms of the Parana Basin by SIB species. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Permian; Serra Alta Formation; Seep fauna; Chemosymbiotic bivalves; Intraplate basin